Maintainability Evaluation for Web Applications - Zaini, Zaida (2006)
Within a short period, the Internet and World Wide Web have become widespread, surpassing all other technological developments in our history. They have also grown rapidly in their scope and extent of use, significantly affecting all aspects of our lives. The scope and complexity of current Web applications is vary, from small-scale to large-scale enterprise applications distributed across the intranets and extranets. As Web applications have evolved, the demands placed on complexity of designing, developing and maintaining have also increased significantly. However, very little has been said about the maintainability factor. Poorly developed Web applications that continue to expand have a high probability of failure. The costs of bad design have many serious consequences.